Examples of the Most Prominent Contemporary Challenges in the Science of Da’wah: نماذج لأبرز التحديات المعاصرة في علم الدعوة - Bn Ghaleb Hassan, Muhammad (AL-HIKMAH: INTERNATIONAL JOURNAL OF ISLAMIC STUDIES AND HUMAN SCIENCES, 2021)
تعرض الباحث في بحثه إلى بيان تعاريف الدعوة وأهميتها، ومنزلتها في الشريعة الإسلامية. وتحدث في البحث عن أبرز التحديات التي تواجه الدعوة المعاصرة والتي تتمثل في المطالب الثلاثة وهي: المطلب الأول: التحديات في الساحة الدعوية. المطلب الثاني: التحديات في المؤلفات الدعوية. المطلب الثالث: التحديات في تأهيل الدعاة. تطرق في المطلب الأول إلى أبرز التحديات في الميدان الدعوي، ومن ذلك تعدد وجود المناهج المخالفة والتي تخالف المنهج العلمي والوسطي الذي جاء به الإسلام. واقترح الباحث عدة حلول في ذلك، منها: أولا: قيام الجهات الحكومية الدينية بدورها الفعال في مراقبة الأنشطة الدعوية والتوعية بخطر الحزبيات الدعوية. وفي المطلب الثاني بيّن الباحث أهمية التأليف في علم الدعوة ، وبيّن الخلل الواقع في هذا الباب والمتمثل في: التأليف المتكرر لنفس المسائل، والمؤلفات التي تحمل نصرة المناهج الباطلة، وذكر جملة من الاقتراحات في ذلك. وفي الثالث: تحدث الباحث عن أهمية تأهيل الدعاة التأهيل العلمي والتقني والمعرفي، لمواكبة تطورات العصر، وتقدم العلوم. ثم ختم بحثه بالنتائج التي توصل إليها، سائلا الله للجميع التوفيق والسداد. الكلمات المفتاحية: الدعوة، التحديات، المناهج المخالفة Abstract In his research, the researcher discussed the definitions of Dawah (calling to Allah), its importance, and its status in Islamic legislation. He spoke in his research about the most prominent challenges that face modern-day Dawah, which are represented by three issues, and they are: The first issue: Challenges in the field of Dawah. The second issue: Challenges in authored books concerning Dawah. The third issue: Challenges in preparing callers to Allah. In his discussion of the first issue, he touched upon the most prominent challenges in the field of Dawah, from which is the multiplicity and presence of opposing Manahij (the way groups of people choose to practice religion, and their beliefs) that are against the scholastic and moderate Manhaj that Islam came with. The researcher also suggested several solutions for that, from amongst them is: Firstly: Governmental religious authorities should play an active role in monitoring religious activities and raising awareness of the dangers of dawah partisans. In his discussion of the second issue, the researcher clarified the importance of authoring books in the science of Dawah, and clarified the flaw present in this field, which is: Repetitive authorship of the same issues and books that aid false manahij, and presented a group of suggestions concerning that. And in the discussion of the third issue: The researcher spoke about the importance of preparing and qualifying callers to Allah, a scholastic preparation, a technical preparation, and a knowledge-related preparation, and that is to enable them to keep pace with the developments of the time, and the advancement of sciences. And finally, he ended his research with the conclusions he reached, asking Allah tawfeeq and correctness for all Keywords: Dawah, Challenges, Multiplicity